Optimal Delay Time of CT Perfusion for Predicting Cerebral Parenchymal Hematoma After Intra-Arterial tPA Treatment - Wu, Bing; Liu, Nan; Wintermark, Max; Parsons, Mark W.; Chen, Hui; Lin, Longting; Zhou, Shuai; Hu, Gang; Zhang, Yongwei; Hu, Jun; Li, Ying; Su, Zihua; et al. (Frontiers in Neurology, 2018)
Background and Purpose— Cerebral hemorrhage is a serious potential complication of stroke revascularization, especially in patients receiving intra-arterial tissue-type plasminogen activator (tPA) therapy. We investigated the optimal pre-intervention delay time (DT) of computed tomography perfusion (CTP) measurement to predict cerebral parenchymal hematoma (PH) in acute ischemic stroke patients after intra-arterial tissue plasminogen activator (tPA) treatment. Methods— The study population consisted of a series of patients with acute ischemic stroke who received intra-arterial tPA treatment and had CTP and follow-up computed tomography/magnetic resonance imaging (CT/MRI) to identify hemorrhagic transformation. The association of increasing DT thresholds (>2, >4, >6, >8, and >10 seconds) with PH was examined using receiver operating characteristic (ROC) analysis and logistic regression. Results— Of 94 patients, 23 developed PH on follow-up imaging. Receiver operating characteristic analysis revealed that the greatest area under the curve for predicting PH occurred at DT > 4 sec (area under the curve, 0.66). At this threshold of > 4 sec, DT lesion volume ≥30.85 mL optimally predicted PH with 70% sensitivity and 59% specificity. DT > 4 sec volume was independently predictive of PH in a multivariate logistic regression model (P<0.05). Conclusions— DT > 4 sec was the parameter most strongly associated with PH. The volume of moderate, not severe, hypo-perfusion on DT is more strongly associated and may allow better prediction of PH after intra-arterial tPA thrombolysis.